Calculation of Pension Funds Using the Unit Credit Method - Anugerah Putri, Sherina (Operations Research: International Conference Series, 2020)
Everyone certainly wants a welfare in the future, including employees. The company provides a pension program as a form of the company’s concern for its employees. This pension fund provides pension benefits to employees at the time of retirement. Funding for this pension requires actuarial calculations which are normal costs and actuarial obligations. This discussion aims to calculate the amount of normal costs and actuarial obligations that must be incurred. The method used in this discussion is the ordinary credit unit method and projecting credit units by analyzing the use of actuarial formulas from several literature studies. In the first discussion using the ordinary credit unit method, the total actuarial liability on 1/1/95 is IDR. 405,355, while in the second discussion using the projecting credit unit method, the normal cost for 1994 on 1/1/94 is IDR 1071, 42. It is hoped that this discussion can increase the reader’s knowledge of pension fund mathematics, especially to determine normal costs and also the value of actuarial obligations using the ordinary credit unit method or the projecting credit unit method.